1991
DOI: 10.1016/0142-9612(91)90074-k
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Escherichia coli on to a series of poly(methacrylates) differing in charge and hydrophobicity

Abstract: The adhesion of three Escherichia coli strains on to six poly(methacrylates) differing in hydrophobicity and surface charge was measured as a function of time under laminar flow conditions. Polymers used were poly(methyl methacrylate) (PMMA), poly(hydroxyethyl methacrylate) (PHEMA) and copolymers of MMA or HEMA with either 15% methacrylic acid (MAA) or 15% trimethylaminoethyl methacrylate-HCl salt (TMAEMA-Cl). Bacterial and polymer surfaces were characterized by means of water contact angles and zeta potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(85 citation statements)
references
References 29 publications
6
75
1
Order By: Relevance
“…51 Thus, according to some authors, a higher bacterial adhesion may be expected for the most hydrophobic PBA surface than for bare titanium. 52 However, our results showed lower adhesion when titanium was covered by the polymer. This supports the assumption that there is no simple relationship to correlate bacterial properties and surface energy of a substratum immersed in a protein-containing medium with bacterial adhesion.…”
Section: Discussioncontrasting
confidence: 52%
“…51 Thus, according to some authors, a higher bacterial adhesion may be expected for the most hydrophobic PBA surface than for bare titanium. 52 However, our results showed lower adhesion when titanium was covered by the polymer. This supports the assumption that there is no simple relationship to correlate bacterial properties and surface energy of a substratum immersed in a protein-containing medium with bacterial adhesion.…”
Section: Discussioncontrasting
confidence: 52%
“…52,53 Thus, these interactions promote, in this particular case, the adhesion to the Au cap where the AgNPs are attached (Figure 4 As the microbots contain Fe as a sandwitched material (Au/Fe/Mg) on the particle, AgNPs coated Janus microbots are capable to remove the bacteria from contaminated solutions using their magnetic properties. Figure 5A and Video S3 display a microbot externally guided using a simple permanent neodymium magnet.…”
Section: Resultsmentioning
confidence: 99%
“…Marshall (1984) proposed that electrokinetic properties were a major factor in the attraction or repulsion of bacterial cells to surfaces. Several studies have indicated that bacterial adhesion negatively correlated with bacterial zeta potentials (van Loosdrecht et al 1989;Tsuneda et al 2003;Li and Logan 2004;Tsuneda et al 2004;Eboigbodin et al 2005), conversely, other studies have been reported that there are no relationship between the two parameters (Abbot et al 1983;Hogt et al 1985;Harkes et al 1991). A review by Donlan (2002) has discussed the contribution of bacterial fi mbriae in the surface attachment mechanism.…”
Section: Introductionmentioning
confidence: 99%